2015
DOI: 10.1021/acsami.5b05555
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Zigzag Film Growth Behaviors in Layer-by-Layer Self-Assembly of Small Molecules through a High-Gravity Technique

Abstract: The zigzag film growth behavior in the layer-by-layer (LbL) assembly method is a ubiquitous phenomenon for which the growth mechanism was rarely investigated, especially for small molecules. To interpret the zigzag increasing manner, we hypothesized that the desorption kinetics of small molecules was dominant for the film growth behavior and demonstrated this hypotheis by introducing the high-gravity technique into the LbL assembly of a typical polyelectrolyte/small molecule system of polyethylenimine (PEI) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…In particular, we have shown that when a PE is adsorbed on a PPCs layer, it can complex the PE of the PPCs, which releases the protein and causes a decrease of the multilayer mass . Similar phenomena have been reported in PEMs, especially for systems containing small molecules, where typical stepwise curves in a sawtooth profile (adsorption–desorption steps) were observed . In a previous study, we suggested that this mechanism is a function of the PE–PE ion-pairing strength compared to the protein–PE pairing strength .…”
Section: Results and Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In particular, we have shown that when a PE is adsorbed on a PPCs layer, it can complex the PE of the PPCs, which releases the protein and causes a decrease of the multilayer mass . Similar phenomena have been reported in PEMs, especially for systems containing small molecules, where typical stepwise curves in a sawtooth profile (adsorption–desorption steps) were observed . In a previous study, we suggested that this mechanism is a function of the PE–PE ion-pairing strength compared to the protein–PE pairing strength .…”
Section: Results and Discussionsupporting
confidence: 76%
“…73 Similar phenomena have been reported in PEMs, especially for systems containing small molecules, where typical stepwise curves in a sawtooth profile (adsorption−desorption steps) were observed. 74 In a previous study, we suggested that this mechanism is a function of the PE−PE ion-pairing strength compared to the protein−PE pairing strength. 73 This hypothesis is in line with the difference in desorption observed for PAH compared to Chi, and for LL-37 compared to Ins and Gox.…”
Section: ■ Introductionmentioning
confidence: 93%
“…Some polymer combinations that grow exponentially using immersive LbL assembly grow linearly under high-gravity assembly . With long enough assembly times, complete desorption of polymers can be engineered with high gravity, rather than the partial desorption seen with many LbL techniques . An issue with high-gravity spin assembly is the requirement for the creation of a custom spinning machine, in comparison to standard spin assembly (with horizontal substrates) machines that are relatively common in research and industry settings.…”
Section: Conventional Lbl Assemblymentioning
confidence: 99%
“…Layer-by-layer (LbL) electrostatic self-assembly technique has received immense scientific and technological interest as a facile and powerful approach to preparing materials with tailored properties [18,19,20]. In the LbL assembly procedure, oppositely charged polyelectrolytes are alternately deposited on a pre-charged substrate to generate a nanometer-scale polyelectrolyte film on its surface.…”
Section: Introductionmentioning
confidence: 99%